Model of Integrated System for Feeding Catfish and Monitoring Pond Temperature Based on IoT - Turnip, Franklin; Suryoatmojo, Jason Rafif Pangestu; Nuris, Nuris; Nugroho, Eddy Prasetyo (Journal of Electronics Technology Exploration, 2024)
Indonesia is renowned for its rich biodiversity, including a diverse array of ornamental and consumable fish species. These fish are widely cultivated in aquariums, ponds, and cages, with prices varying greatly depending on the species. However, the current method of manual fish feeding remains inefficient and time-consuming. To address this challenge, an automated fish feeding system has been developed to streamline and enhance the feeding process.This research project was conducted using a simulation approach to lay the groundwork for a future prototype. The simulation involves an IoT-based model capable of providing automated feeding for catfish and monitoring the temperature of their pond. The system is designed for future implementation at Botani UPI, where traditional manual feeding methods are still prevalent.The primary objectives of this research are to automate catfish feeding and monitor the temperature of their pond. Feed will be dispensed according to a predetermined schedule stored in a database, allowing for flexible adjustments via the internet.Testing has demonstrated the successful operation of the website, fulfilling its core functions: adjusting pond water temperature as needed, automatically providing catfish feed, and scheduling regular feeding intervals. Users can control these functions remotely, enabling effective pond monitoring and management without physically being present at the site.The success of this testing underscores the immense potential of the integrated system to elevate catfish farming productivity and efficiency. By maintaining optimal pond temperatures, the health and growth of catfish can be better sustained, while scheduled and accurate feeding helps minimize feed wastage and ensures adequate nutrition for the fish. Additionally, the system reduces the manual workload for farmers, allowing them to focus on other aspects of pond management. Overall, the implementation of this technology not only offers economic benefits through increased production yield but also promotes more sustainable and modern fish farming practices.